The Effects of Chile S 2005 Traffic Law Reform and In-Country Socioeconomic Differences on Road Traffic Deaths Among Children Aged 0-14 Years: A 12-Year Interrupted Time Series Analysis - Martinez-Diaz, P; Contreras-Ramirez, D (Elsevier Ltd, 2020)
Objectives: This study assessed the effect of Chile s 2005 traffic law reform (TLR) on the rates of road traffic deaths (RTD) in children aged 0–14 years, adjusting for socioeconomic differences among the regions of the country. Methods: Free-access sources of official and national information provided the data for every year of the study period (2002–2013) and for each of the country s 13 upper administrative divisions with respect to RTD in child pedestrians and RTD in child passengers (dependent variables), and the following control variables: the number of road traffic tickets processed, investment in road infrastructure, poverty, income inequality, insufficient education, unemployment, population aged 0–14 years, and prevalence of alcohol consumption in the general population. Interrupted time series analyses (level and slope change impact model), using generalized estimating equation methods, were conducted to assess the impact of the TLR (independent variable) on the dependents variables. Results: There was a significant interaction between time and Chile s 2005 TLR for a reduction in child pedestrians (incidence rate ratio [IRR] 0.87, 95% confidence interval [CI] 0.79-0.96) and passengers RTD (IRR for interaction 0.80, 95% CI 0.67-0.96) trends. In addition, in child pedestrians, RTD rates were affected by poverty (IRR 1.04, 95% CI 1.02–1.05), income inequality (IRR 1.02, 95% CI 1.00–1.04), and unemployment (IRR 0.94, 95% CI 0.90-0.98), whereas in the case of child passengers, poverty (IRR 1.05, 95% CI 1.01–1.08) and income inequality (IRR 0.93, 95% CI 0.91-0.95) were significant. Conclusions: Large-scale legislative actions can be effective road safety measures if they are aimed at promoting behavioral change in developing countries, improving the safety of children on the road. Additionally, regional socioeconomic differences are associated with higher RTD rates in this population, making this an argument in favor of road safety policies that consider these inequalities. The number of road traffic tickets processed and the investment in road infrastructure were not significant. © 2019